Segregation for sexual seed production in Paspalum as directed by male gametes of apomictic triploid plants - Martínez, Eric Javier (2007)
Fil: Martínez, Eric Javier. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.